An Uphill Battle : Homelessness in Canada and Quebec and Its Likely Impact on the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2024)
Keywords: Official Language Minority Community (OLMC)

Un défi de taille : Le sans-abrisme au Canada et au Québec et son impact potentiel sur la communauté québécoise d’expression anglaise - Quebec Community Groups Network (QCGN) (2024)
Keywords: Official Language Minority Community (OLMC)

Mise à jour au sujet des frais de scolarité : Le gouvernement choisit une voie susceptible de ruiner les universités anglophones du Québec - Quebec Community Groups Network (QCGN) (2023)

Community Vitality & Acceptability of English Canadian Migrants Rated by Québecois Francophone, Acadian and Franco-Ontarian University Students - Bourhis, Richard Y.; Sioufi, Rana; Allard, Réal (QUESCREN Education and Vitality Forum 2023, 2023)

Senate Standing Committee on Social Affairs, Science and Technology : Study on Bill C-35, An Act respecting early learning and child care in Canada - Quebec Community Groups Network (QCGN) (2023)

Déclaration du QCGN à l’occasion de la nomination des nouveaux secrétaires parlementaires - Quebec Community Groups Network (QCGN) (2023)

QCGN Statement on Appointment of New Parliamentary Secretaries - Quebec Community Groups Network (QCGN) (2023)

Three Approaches to Writing School Programs with Official Language Minorities : Research Brief no. 9 - Gani, Raphaël (Quebec English-speaking Communities Research Network (QUESCREN), 2023)
Keywords: Official Language Minority Community (OLMC)

Trois approches pour rédiger des programmes scolaires avec les minorités de langue officielle : Résumé de recherche no. 9 - Gani, Raphaël (Quebec English-speaking Communities Research Network (QUESCREN), 2023)
Keywords: Official Language Minority Community (OLMC)

Le QCGN félicite Randy Boissonault pour sa nomination au poste de nouveau ministre fédéral des Langues officielles - Quebec Community Groups Network (QCGN) (2023)

QCGN Welcomes Randy Boissonnault as the new Federal Minister of Official Languages - Quebec Community Groups Network (QCGN) (2023)

Senate Standing Committee on Official Languages (OLLO) : Study of C-13 An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2023)
The QCGN has participated in every step of the modernization of the Official Languages Act, beginning with Bill S-209; an initiative of this Chamber led by the Honourable Maria Chaput. English-speaking Quebec worked closely and in good faith with our Francophone counterparts in the rest of Canada, Ministers of Canadian Heritage and Official Languages and this Committee during its historic study to modernize the Act, beginning in 2017.

Définir les règlements de la partie vii de la Loi sur les langues officielles : Enjeux pour le Québec d’expression anglaise lors du processus - Quebec Community Groups Network (QCGN) (2023)

Producing Regulations for Part VII of the Official Languages Act : English-speaking Quebec’s Stake in the Process - Quebec Community Groups Network (QCGN) (2023)

Le QCGN prie instamment les parlementaires de garantir un avenir où le Québec d'expression anglaise est reconnu comme partenaire égal dans la nouvelle loi sur les langues officielles - Quebec Community Groups Network (QCGN) (2022)

QCGN Urges Parliamentarians to Guarantee Future of English-speaking Quebec as Equal Partner in New Official Languages Act - Quebec Community Groups Network (QCGN) (2022)

Brief to the House of Commons Standing Committee on Official Languages on the Topic of Bill C-13, an Act To Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses and to Make Related Amendments to Other Acts - O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
The present brief focuses on the first purpose, Bill C-13 amendments to the OLA. This is the topic on which I in my role as research associate at the Quebec English-Speaking Communities Research Network (QUESCREN) have developed the most knowledge.

Mémoire présenté au Comité permanent des langues officielles de la Chambre des communes au sujet du projet de loi C-13 : Loi modifiant la Loi sur les langues officielles, édictant la Loi sur l’usage du français au sein des entreprises privées de compétence fédérale et apportant des modifications connexes à d’autres lois - O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
Le présent mémoire est axé sur le premier objectif — les modifications apportées à la LLO par le projet de loi C-13 —, car il s’agit du sujet sur lequel j’ai développé le plus de connaissances à titre d’attachée de recherche pour le Réseau de recherche sur les communautés québécoises d’expression anglaise (QUESCREN)

Modernizing the Official Languages Act : How the Federal Government Got it Wrong with C-13 - Quebec Community Groups Network (QCGN) (2022)

Legislative Brief to House of Commons and Senate Standing Committee(s) on Official Languages : Bill C-13, An Act to amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to other Acts (short title: An Act for the Substantive Equality of Canada’s Official Languages) - Task Force on Linguistic Policy (2022)
The TFLP submits that Bill C-13, the proposed modernization of the Official Languages Act (“OLA”), redefines and restructures Canada’s federal Official Languages framework in fundamental and, likely, undesirable ways. It introduces an unprecedented asymmetrical approach to the protection and promotion of Official Languages in Canada and, perhaps even more problematically, to the defence of the linguistic rights and recourses afforded to French speakers and English speakers, both in the Province of Québec, and across the country.

Linguistic Diversity and Use of English and French in Canada : 2021 Census of Population - Quebec Community Groups Network (QCGN) (2022)

Use of French in Federally Regulated Private Businesses Act Abandons English-speaking Quebecers, QCGN Tells Senate Committee - Quebec Community Groups Network (QCGN) (2022)

Le QCGN propose des modifications majeures au projet de loi fédéral visant à moderniser la Loi sur les langues officielles - Quebec Community Groups Network (QCGN) (2022)

QCGN Proposes Major Amendments to Federal Bill Modernizing the Official Languages Act - Quebec Community Groups Network (QCGN) (2022)

Perceptions de la migration interprovinciale des Canadiens anglais et Canadiens pour la vitalité des Québécois, Acadiens et Franco-ontariens - Bourhis, Richard Y.; Sioufi, Rana (2022)

Brief to House of Commons Standing Committee on Official Languages : Bill C-13, An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2022)
The Official Languages Act is a lifeline for English-speaking Quebec. With Quebec’s Bill 96, the community needs this lifeline more than ever. But with Bill C-13, this lifeline is fraying. Founded in 1995, the Quebec Community Groups Network (“QCGN”) is a not-for-profit organization linking English-language community organizations across Quebec. The QCGN—like the community it serves—is proud to support the protection and promotion of the French language in Canada. The QCGN advocates for linguistic duality in every province and territory. The English-speaking minority in Quebec is a diverse, bilingual, and resilient community that is facing serious economic challenges—in the face of persistent myths and stereotypes. Although the English language itself is not threatened, the English-speaking community’s challenge is in maintaining the community’s vitality and survival in all regions of Quebec.
Keywords: Official Language Minority Community (OLMC)

Mémoire présenté au Comité permanent des langues officielles de la Chambre des communes : Projet de loi C-13, Loi visant l’égalité réelle entre les langues officielles du Canada - Quebec Community Groups Network (QCGN) (2022)
La Loi sur les langues officielles (LLO) représente une bouée de sauvetage pour le Québec d’expression anglaise et, compte tenu du projet de loi 96 du Québec, la communauté anglophone en a besoin plus que jamais. Mais avec le projet de loi C-13, cette bouée de sauvetage s'effiloche. Fondé en 1995, le Quebec Community Groups Network (QCGN) est un organisme à but non lucratif qui relie les organismes communautaires de langue anglaise partout au Québec. Le QCGN — tout comme les communautés qu'il sert — est fier de soutenir la protection et la promotion de la langue française au Canada. Le QCGN milite en faveur de la dualité linguistique dans chaque province et chaque territoire. La minorité d’expression anglaise du Québec est une communauté diversifiée, bilingue et résiliente, qui est confrontée à de sérieux défis économiques ainsi qu’à des mythes et à des stéréotypes persistants. Bien que sa langue elle-même ne soit pas menacée, le défi de la communauté d’expression anglaise consiste à préserver sa vitalité et sa survie dans toutes les régions du Québec.
Keywords: Official Language Minority Community (OLMC)

Le QCGN réagit à la Loi modifiant la Loi sur les langues officielles et édictant la Loi sur l'utilisation du français dans les entreprises privées sous réglementation fédérale - Quebec Community Groups Network (QCGN) (2022)

QCGN Reacts to An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Business Act - Quebec Community Groups Network (QCGN) (2022)

The Tourist Offer of the Whiteley Museum and its Surrounding Area on the Lower North Shore : A Quality Improvement Report - Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
This report analyzes the tourist offer in the eastern part of Quebec’s Lower North Shore, particularly the municipality of Bonne-Espérance, a region where English speakers make up the majority of the population. It focuses specifically on an institution in one of these municipalities, the Whiteley Museum. The report provides the authors’ suggestions to improve tourism development as a means to diversify the economy, potentially help reverse demographic decline, and build community vitality.

Understanding the Long-term Care Experience of Official Language Minorities in Canada: An Environmental Scan - Hsu, Amy T.; Ménard, Alixe; Scott, Mary (2022)
Members of minority and racialized communities across Canada commonly experience disparities in health and healthcare. In the context of the COVID-19 pandemic, minority and racialized individuals have been found to report poorer health outcomes and added barriers to healthcare access. While there is growing understanding of the impact of COVID-19 on individuals who live and work in residential long-term care (LTC) homes and other congregate care settings, little attention has been directed at examining inequities in the care experience and care-related outcomes that equity-seeking groups, including Official Language Minority Communities (OLMC), face within LTC. It’s clear that there is a need for systemic change within LTC; the pandemic, especially in its first two waves, highlighted several pre-existing issues within this sector. To ensure high-quality and equitable care for all aging Canadians, these system-level changes must be informed by evidence.
Keywords: Official Language Minority Community (OLMC)

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Dre. Amy T; Ménard, Alixe; Scott, Mary (2022)
Les membres des communautés racisées et en situation minoritaire du Canada vivent souvent des disparités en matière de santé et de soins de santé. Dans le contexte de la pandémie de COVID-19, on a constaté que les personnes membres d’une minorité et les personnes racisées signalaient de moins bons résultats de santé et des barrières supplémentaires à l’accès aux soins de santé. Bien que l’on comprenne de plus en plus l’incidence de la COVID-19 sur les personnes vivant et travaillant dans des établissements de soins de longue durée (SLD) et dans d’autres établissements de soins collectifs, on a porté peu d’attention à l’examen des inégalités dans l’expérience des soins et des résultats liés aux soins auxquels font face les groupes en quête d’équité, y compris les communautés de langue officielle en situation minoritaire (CLOSM). Il est clair qu’il faut apporter des changements systémiques au sein du secteur des SLD; la pandémie, surtout au cours de ses deux premières vagues, a mis en lumière plusieurs problèmes préexistants dans ce secteur. Pour assurer des soins de grande qualité et équitables pour tous les Canadien(ne)s âgés, ces changements au niveau du système doivent être fondés sur des données probantes.
Keywords: Official Language Minority Community (OLMC)

Not Your Typical Self-Care Seminar : Prioritizing Connection Over Information - Joanisse, Mélanie (2022)

Message du QCGN à Air Canada : Une simple excuse ne peut réparer les dommages causés au Québec d’expression anglaise - Quebec Community Groups Network (QCGN) (2021)

QCGN to Air Canada : Apology Alone Cannot Undo Damage to English-speaking Quebec - Quebec Community Groups Network (QCGN) (2021)

Le QCGN est impatient de collaborer avec Ginette Petitpas Taylor, nouvelle ministre des Langues officielles - Quebec Community Groups Network (QCGN) (2021)

QCGN Eager to Collaborate with New Official Languages Minister Ginette Petitpas Taylor - Quebec Community Groups Network (QCGN) (2021)

Le Quebec Community Groups Network félicite les partis qui ont participé à l’élection fédérale - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network Congratulates Parties for Federal Election - Quebec Community Groups Network (QCGN) (2021)

Le Quebec Community Groups Network encourage les Québécois d’expression anglaise à voter pour le meilleur candidat local - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network Urges English-speaking Quebecers to Vote for Best Local Candidate - Quebec Community Groups Network (QCGN) (2021)

Le QCGN demande aux partis et aux candidats fédéraux de défendre les droits linguistiques des Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2021)

QCGN Statement on Government of Canada’s Proposed Changes to the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

QCGN Statement on Murder of Muslim Family in London, Ontario : Human Rights and Freedoms Are Not to be Taken for Granted - Quebec Community Groups Network (QCGN) (2021)

QCGN Supports Commissioner's Call for Symmetry in the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

Many Reasons to Participate in Census - Quebec Community Groups Network (QCGN) (2021)
Keywords: Official Language Minority Community (OLMC)

What Exactly is the Notwithstanding Clause, and Why Does it Matter? - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network analyse préliminaire du projet de loi C-13 : Loi visant l’égalité réelle entre les langues officielles du Canada - Quebec Community Groups Network (QCGN) (2021)
Rappelons que le présent document offre un aperçu du projet de loi C-13. Il ne s'agit pas d'une analyse exhaustive du projet de loi. Elle soutient et s’oriente plutôt vers les domaines prioritaires du QCGN.

Quebec Community Groups Network Preliminary Analysis of Bill C-13 : An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2021)
This document presents an overview of Bill C-13. This is not a comprehensive analysis of the Bill. Rather, it is informed and directed at priority areas of the QCGN.

Understanding an Official Language Minority Community - Quebec Community Groups Network (QCGN) (2021)
Keywords: Official Language Minority Community (OLMC)

Federally Regulated Businesses and the New Languages Landscape - Quebec Community Groups Network (QCGN) (2021)

English and French : Towards the Substantive Equality of Official Languages in Canada - Quebec Community Groups Network (QCGN) (2021)
The Government of Canada’s paper on official language reform captures important demands made by the English-speaking community of Quebec during consultative processes related to the modernization of the Official Languages Act. There is reason for optimism around proposals for an expanded role of Treasury Board and power of the Commissioner of Official Languages in the implementation of the Act. And there are opportunities for increased support to our community’s institutions and provisions for more transparency on federal transfers directed towards our vitality; proposals that are tempered by the need for provincial cooperation.

By the Numbers : How are Communities Counted? - Quebec Community Groups Network (QCGN) (2021)

Canada Must Not Abandon its Leadership on Official Languages - Quebec Community Groups Network (QCGN) (2021)

Government Must Not Territorialize the Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Huge Victory for Minority School Boards in Supreme Court B.C. School Board Case - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

FAQ Regarding the Canadian Emergency Response Benefit (CERB) Program - McSween, Pierre-Yves (2020)
Disclaimer: This document has been prepared with the information in public circulation as of March 26, 2020. This is not an official communication from the government and information presented here is not to be used as proof of eligibility. YES has translated and edited the original text for clarity. This information is provided solely as a resource. As this is an evolving document, the user of this information is responsible for determining and verifying the accuracy of the data presented here and how it is used.

How Powers are Divided Between our Federal and Provincial Governments - Quebec Community Groups Network (QCGN) (2020)

Black-White Differences in Canadian Educational Attainments and Earnings - Masella, Rosalie; McIntosh, James (Collaborative Unity and Existential Responsibility, 2019)
Data from two large Canadian surveys are used to analyze educational and earnings performance of Blacks and Whites. The main purpose of this study is to determine how well blacks perform relative to Whites in these two areas.

QCGN Intervienes in B.C. School Board Case at Supreme Court of Canada - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

Memorandum of Understanding Between Acadians in New Brunswick, English-speaking Quebecers and Franco-Ontarians - Société de l’Acadie du Nouveau-Brunswick (SANB); Quebec Community Groups Network (QCGN); Assemblée de la francophonie de l’Ontario (AFO) (2019)
Keywords: Official Language Minority Community (OLMC)

Le Canada de Minnie H. Bowen : Cahier de l'enseignant pour le primaire - Eastern Townships Resource Centre (ETRC) (2019)

Le Canada de Minnie H. Bowen : Cahier de l'enseignant pour le secondaire - Eastern Townships Resource Centre (ETRC) (2019)

Le Canada de Minnie H. Bowen : Dossier de l'élève pour le primaire - Eastern Townships Resource Centre (ETRC) (2019)

Le Canada de Minnie H. Bowen : Dossier de l'élève pour le secondaire - Eastern Townships Resource Centre (ETRC) (2019)

Le Canada de Minnie H. Bowen : Dossier documentaire pour le primaire - Eastern Townships Resource Centre (ETRC) (2019)

Le Canada de Minnie H. Bowen : Dossier documentaire pour le secondaire - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Documentary Record for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Documentary Record for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Student's Workbook for Elementary - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Student's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for elementary school - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Message For Our Veterans - Maurice, Cornella (2019)

Neighbours of Rouyn-Noranda Guide to Federal Election Candidates for Abitibi-Téscamingue - Neighbours Regional Association of Rouyn-Noranda (2019)
Here is a brief guide to your candidates for the Abitibi-Témiscamingue riding, and some of the party platforms on key issues. Neighbours remains non-partisans and is only attempting to provide information not an endorsement.

Y4Y Quebec Opposes the Cancellation of the French-language University in Ontario and Expresses its Solidarity with the Young Franco-Ontarians Who Worked on the Project - Youth for Youth Québec (Y4Y Québec) (2018)

QCGN Denounces Cuts to French Language Services in Ontario - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

[Letter to René Cormier, Chair of the Senate Standing Committee on Official Languages, from Geoffrey Chambers, QCGN President, re: the Official Languages Act] - Chambers, Geoffrey (2018)

An Independent Report of the History Experts Committee On the Provincial History of Québec and Canada Program and Approved English Textbooks - Commission scolaire English-Montreal / English Montreal School Board (2018)
In September 2017, the Ministry of Education implemented a revised Secondary III and IV compulsory History of Québec and Canada program. This program raised a number of issues that became of concern to the English Montreal School Board (EMSB). Given these concerns, the EMSB commissioned an independent History Experts Committee to review the content of this program as well as the Ministry-approved English-language textbooks. The following is a summary of the findings of this Committee

Brief by the Consortium of Official Language Minority Community Media, Presented to the Standing Senate Committee on Official Languages Within the Context of its Study on Canadians' Views About Modernizing the Official Languages Act - Sonier, Francis; Demers, Paul; Bonspiel, Steve (2018)
The Consortium of Official Language Minority Community Media (the Consortium) is an alliance of the three national organizations representing official language minority community media in Canada: the Association de la presse francophone (APF), the Alliance des radios communautaires du Canada (ARC du Canada) and the Quebec Community Newspapers Association (QCNA). Since 2016, the Consortium has been the common voice of all three of its members on a number of issues.
Keywords: Official Language Minority Community (OLMC)

QCGN Applauds Priorities in Commissioner's Annual Report - Quebec Community Groups Network (QCGN) (2018)

Message For Our Veterans - Maurice, Cornella (2018)

QCGN Project to Involve Youth in Canada's Sesquicentennial - Quebec Community Groups Network (QCGN) (2017)

QCGN Invites Meilleur to Become Acquainted with English-speaking Quebec - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Hopeful About Opportunities for Official Language Minority Communities in Federal Budget - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

Bilingual Young Quebecers Leading the Way to Canada's Future - Quebec Community Groups Network (QCGN) (2017)

QCGN Welcomes Resurrection of Independent Court Challenges Program - Quebec Community Groups Network (QCGN) (2017)

English-speaking Quebec Must Have a Stronger Voice in Conversation About Official Languages - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Public Consultation on Canadian Content in a Digital World - English Language Arts Network (ELAN); Forget, Bettina; Rodgers, Guy (2016)
Keywords: Official Language Minority Community (OLMC)

QCGN Advocates for More Flexible Regulations for Provision of Federal Minority Language Services - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Brief to the House of Commons Special Committee on Electoral Reform - Quebec Community Groups Network (QCGN) (2016)
The QCGN is concerned that the Government of Canada has not provided Canadians a specific electoral system on which to be consulted. Arriving at a recommended electoral system has been delegated to this Committee, with the decision on which system to pursue resting with the government. Members of the Committee undoubtedly understand the complexity of various systems under consideration, and the esoteric nature of the material. Indeed, so far the discussion at this Committee has been dominated by specialists, a term used broadly to include technical experts, and people and groups with an ongoing interest and specialization in electoral systems. This should come as no surprise when beginning with a blank sheet of paper, and indeed, the Committee is mandated to seek out expert testimony.

Quebec Youth Lead the Way to Sesquicentennial Celebrations - Quebec Community Groups Network (QCGN) (2015)

AELAQ Reading Fund Covers Honoraria and Travel Costs for Public Readings Across Canada - Association of English-language Publishers of Quebec (AELAQ) (2015)

Public Readings by Authors Published by Members of the Association of English-language Publishers of Quebec (AELAQ) - Association of English-language Publishers of Quebec (AELAQ) (2015)
Keywords: Official Language Minority Community (OLMC)

Message For Our Veterans - Maurice, Cornella (2015)

Federal Institutions Must Properly Support Quebec's English-speaking Seniors, says Graham Fraser - Office of the Comissioner of Official Languages (2013)

QCGN Congratulates Shelly Glover New Minister for Canadian Heritage and Official Languages - Quebec Community Groups Network (QCGN) (2013)
Keywords: Official Language Minority Community (OLMC)

Le Canada, le bilinguisme et le commerce - Arcand, Alan; Le Conference Board du Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
Le français est l’une des principales langues mondiales. Selon l’Organisation internationale de la francophonie (OIF), au moins 220 millions de personnes le parlent dans le monde1. C’est la langue officielle de tous les organismes des Nations unies et d’un grand nombre d’organisations internationales. Le français a pris naissance en France et s’est répandu grâce à l’expansion de ce pays outre-mer. Actuellement, quelque 30 pays dans le monde, dont le Canada, comptent le français parmi leurs langues officielles.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Feasibility Study for a Rapid Maritime Link for Passengers of the Lower-North-Shore - Conseils & Stratégies pour l'Avenir des Régions (PAR) (2013)
This study relates to the feasibility of a maritime link for passengers on the Lower North Shore aiming at meeting a need shown for accessibility of both citizens and tourist alike with an affordable, rapid link with improved frequency, between the different communities and lasting the summer period, departures from Natashquan and Blanc-Sablon.

QCGN Approves New Roadmap for Canada's Official Languages - Quebec Community Groups Network (QCGN) (2013)

Federal Budget Indicates Government Comitted to Quebec's English-speaking Minority with a Renewed Roadmap for Official Languages - Quebec Community Groups Network (QCGN) (2013)

[Study on the use of the Internet, new media and social media and respect for Canadians' language rights : A study on Air Canada's obligations under the Official Languages Act : Remarks to the Standing Committee on Official Languages] - Quebec Community Groups Network (QCGN) (2011)

Linda Leith Remarks to OCOL Part VII Forum - Leith, Linda (2011)
Keywords: Official Language Minority Community (OLMC)

Roadmap to Canada's Linguistic Duality 2008-2013 - Donnelly, Robert (2010)
Remarks to the Standing Committee on Official Language
Keywords: Official Language Minority Community (OLMC)

The Official Languages Act and the English-speaking Community of Quebec : Learning from the Past - Donnelly, Robert (2010)
Keywords: Official Language Minority Community (OLMC)

The Official Languages Act and the English-speaking Community of Quebec : Looking to the Future - Johnston, Nicola (2010)
Remarks to the Standing Committee on Official Languages

What is Bill C-32? - English Language Arts Network (ELAN) (2010)
Bill C-32 is officially known as the Copyright Modernization Act. It was an attempt at a “Balanced Copyright” act introduced in Parliament on June 2, 2010, by the Conservative Party — Honourable Tony Clement, Minister of Industry, and the Honourable James Moore, Minister of Canadian Heritage and Official Languages. It contains changes to Canadian Copyright Law that are hotly contested by artists and authors of cultural media. The Bloc, NDP and Liberal parties are opposed to the act being passed in its current state, and are calling for amendments to be made.
Keywords: Official Language Minority Community (OLMC)

Comments on the Canada Media Fund's English Regional Production Policies by the English-language Arts Network of Quebec - English Language Arts Network (ELAN) (2009)
The Canadian Television Fund (CTF) has made the English-language regions synonymous with the official-language minority in Quebec. While regional policies overlap with official-language policies in many ways, they are each distinct and need to be addressed differently. The Official Languages Act gives the English-language minority in Quebec the same status as the French-language minority outside Quebec. However, the CTF has not recognized that the official-language minority community (OLMC) in Quebec has the same rights and legal status as the French-language minority outside Quebec. Thus, Montreal production is not given regional status for the BPE, nor is there a Quebec OLMC production fund similar to the production fund (FLPOQ) available to the French-language minority outside Quebec.
Keywords: Official Language Minority Community (OLMC)

Re: Support of the Canadian Broadcasting Corporation (CBC) - Rodgers, Guy (2009)
Keywords: Official Language Minority Community (OLMC)

ELAN Speech to Parliamentary Committee on CBC Review - English Language Arts Network (ELAN) (2007)

Through the Looking Glass : A Comparison of Broadcast License Fees in Canada, Australia, the United Kingdom and the United States - Cox, Kirwan (2004)
The decision of a domestic broadcaster to commission a program from a producer, and the license fee paid by the broadcaster to that producer, is the foundation of the independent television production system in Canada. Most public funding for Canadian programming follows on the basis of these transactions. Unfortunately, that public funding is oversubscribed, and the production industry is chronically underfunded. Some suggest that part of this problem is the size of the Canadian broadcast license fee. Based on anecdotal evidence, it is argued that Canadian license fees are low by international standards. The purpose of this study is to see if Canadian license fees for English independent television programs are indeed low based on selected international and historical comparisons. If they are, why?

Hundreds of Canadian Children Have No Right to Attend English-language Schools in Quebec - Alliance Quebec (AQ) (2003)

The Supreme Court of Canada Agreed to Hear Three Cases Involving 11 Families Who Sought Alliance Quebec's Support in Getting Access to Quebec's English-language School System for Their 25 Children - Alliance Quebec (AQ) (2003)

The Ontario Government Should Fully Respect the Province's French-speaking Minority: AQ - Alliance Quebec (AQ) (2000)

Statement from Alliance Quebec on the Ontario Government's Failure to Grant the New Ottawa Megacity Official BIlingual Status - Alliance Quebec (AQ) (1999)

The Official Languages Act Systematically Violated : The Canada Post Corporation in Quebec - Johnson, William (1999)

How to Celebrate "La Fête Nationale" - Johnson, William (1999)

Border Labour Situation a Threat, Johnson Warns Quebec - Alliance Quebec (AQ) (1999)

Alliance Quebec Makes Case for Canada with Premiers - Alliance Quebec (AQ) (1997)

[An Open Letter from Michael J. Hamelin, President of Alliance Quebec to All Premiers] - Hamelin, Michael J. (1997)

[Letter from Pat Courcelle, President of Société franco-Manitobaine and Michael J. Hamelin, President of Alliance Quebec, to Rt. Hon. Jean Chrétien, Prime Minister of Canada] - Courcelle, Pat; Hamelin, Michael J. (1997)

Alliance Quebec Worried About Federal-Provincial Manpower Talks - Alliance Quebec (AQ) (1996)

Coasters Association Informer - Coasters Association (1996)

Coasters Association Informer - Coasters Association (1995)

Submission to Joint Committee of the House of Commons and the Senate of Canada on a Renewed Canada Submitted by Quebec Federation of Home & School Associations - Quebec Federation of Home and School Associations (QFHSA) (1991)
The mandate of Quebec's Commission on the Constitution was to canvas public opinion around the province, and subsequently to make proposals to the National Assembly for a new constitutional agreement. Premier Robert Bourassa excluded from the options the status quo and annexation to the United States. Quebec Federation of Home & School Associations (OFHSA) would also exclude the model 'national' Sovereignty/Association, i.e., one where there is a common currency and free trade between the provinces but, in sensitive areas where jurisdiction is shared by the federal and provincial governments, such as immigration, manpower, education, communications and the environment, Quebec acquires exclusive political control by a transfer of jurisdictions from the federal level. Such transfers relieve the Federal Government of its constitutional protective obligations in regard to individuals and minorities in Quebec without compensating protection at the provincial level that enables such individuals and minorities to continue to develop and flourish.

Submission to New Brunswick Select Committee on the 1987 Constitutional Accord Submitted by Quebec Federation of Home & School Association - Quebec Federation of Home and School Associations (QFHSA) (1988)
The Quebec Federation of Home & School Associations (QFHSA) is pleased to have the opportunity to make this submission to the Select Committee on Constitutional Reform regarding the 1987 Constitutional Accord.

Brief on the Green Paper of Immigration to the Special Joint Committee on Immigration Policy by Quebec Federation of Home & School Associations - Quebec Federation of Home and School Associations (QFHSA) (1975)
Any new Immigration Act ought to satisfy criteria which will make its spirit easily grasped by all people interested in the subject: it ought to be concise; it ought to spell out clearly a set of positive and basic principles governing regulations which will be issued from time to time to implement the Act - it being recognized that while the regulations themselves must be revised from time to time to make the Act applicable to changing circumstances, yet these must at all time represent in practice the spirit of the Act. Thus we agree with what the Green Paper indicated (Highlights Vol. 1 p. 18).

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1971)

The Royal Commission on Broadcasting - The Canadian Home and School and Parent-Teacher Federation (1956)
The Canadian Home and School and Parent-Teacher Federation, representing 274,693 members organized in 3,672 local associations in nine provincial federations across Canada, (Newfoundland is not presentl:y organized as a Provincial Federation) is pleased to submit this statement of our views with respect to broadcasting in Canada under the terms of Order in Council P.C.1955-1796 of December 2nd,1955

A Day in the Life of a Fisherman

Community Case Studies (Council for Magdalen Islanders (CAMI))
These case studies accompany the section of the literature review that deals with contemporary development in island, remote and rural communities. These excerpts are quoted directly from the article or book they were published in, with the exception of Samsø, Denmark. Italicized text indicates direct quote. A complete reference accompanies each case. Cases are in alphabetical order by community name.

Lunch & Learn : Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada: un état des lieux / Understanding the Long-Term Care Experience of Official Language Minorities in Canada : An Environmental Scan - Ménard, Alixe; Scott, Mary; Hsu, Amy

Development of ABE/Literacy in Canada : A Chronology - Shohet, Linda